Early Context-Conditioned Orthographic Knowledge in European Portuguese: The Spelling of the Schwa - Vale, Ana Paula; Perpétua, Rafaela (Frontiers in Education, 2020)
This longitudinal study examined how phonemic-orthographic context affected the spelling of the schwa by Portuguese beginning spellers at two time points in first grade. The schwa, being phonetically instable and phonologically ill-defined, having an optional unpredictable realization and being frequently deleted at syllable final position, is often spelt as